Solid Self-Nanoemulsifying Drug Delivery Systems of Furosemide: In Vivo Proof of Concept for Enhanced Predictable Therapeutic Response - Sania Gul; Sathvik Belagodu Sridhar; Aamir Jalil; Muhammad Akhlaq; Muhammad Sohail Arshad; Hafiz Shoaib Sarwar; Faisal Usman; Javedh Shareef; Sabin Thomas (MDPI AG, 2024)
Liquid self-nano emulsifying drug delivery systems (SNEDDS) of furosemide (FSM) have been explored as a potential solution for enhancing solubility and permeability but are associated with rapid emulsification, spontaneous drug release, and poor in vivo correlation. To overcome the shortcoming, this study aimed to develop liquid and solid self-emulsifying drug delivery systems for FSM, compare formulation dynamics, continue in vivo therapeutic efficacy, and investigate the advantages of solidification. For this purpose, liquid SNEDDS (L-SEDDS-FSM) were formed using oleic acid as an oil, chremophore EL, Tween 80, Tween 20 as a surfactant, and PEG 400 as a co-surfactant containing 53 mg/mL FSM. At the same time, solid SNEDDS (S-SEDDS-FSM) was developed by adsorbing liquid SNEDDS onto microcrystalline cellulose in a 1:1 ratio. Both formulations were evaluated for size, zeta potential, lipase degradation, and drug release. Moreover, in vivo diuretic studies regarding urine volume were carried out in mice to investigate the therapeutic responses of liquid and solid SNEDDS formulations. After dilution, L-SEDDS-FSM showed a mean droplet size of 115 ± 4.5 nm, while S-SEDDS-FSM depicted 116 ± 2.6 nm and zeta potentials of −5.4 ± 0.55 and −6.22 ± 1.2, respectively. S-SEDDS-FSM showed 1.8-fold reduced degradation by lipase enzymes in comparison to L-SEDDS-FSM. S-SEDDS-FSM demonstrated a sustained drug release pattern, releasing 63% of the drug over 180 min, in contrast to L-SEDDS-FSM, exhibiting 90% spontaneous drug release within 30 min. L-SEDDS-FSM exhibited a rapid upsurge in urine output (1550 ± 56 μL) compared to S-SEDDS-FSM, showing gradual urine output (969 ± 29 μL) till the 4th h of the study, providing sustained urine output yet a predictable therapeutic response. The solidification of SNEDDS effectively addresses challenges associated with spontaneous drug release and precipitation observed in liquid SNEDDS, highlighting the potential benefits of solid SNEDDS in improving the therapeutic response of furosemide.